Interface of teaching foreign languages and university outreach in the context of the Covid-19 pandemic - Aguiar Bellido, Jorge David; da Silva Filomena, Bárbara; dos Santos Gomes, Henrique; Pena Natividade , Flaviana (Guará Journal, 2023)
This article presents an experience report on the “CAP Langua-ge Conversation Center,” an outreach project initiated by the Federal University of São João del Rei, Alto Paraopeba campus, aimed at democratizing the knowledge of foreign languages through cultural and teaching activities. The project has been active since 2014 and focuses on sensitizing society to the importance of learning a second language and promoting internationalization. Amidst the COVID-19 pandemic, the project observed a significant increase in the number of courses and classes offered, as well as the team size and enrollment of in-dividuals in the selection process. Compared to the 2020.1 and 2022.1 public calls, the number of students enrolled increased by 533.75%. The article aims to investigate the impact of the language courses offered by the project. Analyzing the data collected from each public call, it was evident that the project garnered greater visibility for both the project and UFSJ, ena-bling participation from individuals from other universities and states in Brazil, fulfilling its objective of outreach in knowledge diffusion.